2016
DOI: 10.24191/jeeir.v4i1.9074
|View full text |Cite
|
Sign up to set email alerts
|

Global Financial Crisis (GFC) And Islamic Banks Profitability: Evidence From MENA Countries

Abstract: This  paper investigate the determinant of profitability of Islamic banks from the MENA region and how Global Financial Crisis (GFC) impacts on their performance. The study covers 117 banks for periods of  2003 to 2011. To examine the determinant of Islamic banking profitability (ROA), we apply a balanced and dynamic panel data regression model. We  conclude that the profitability of Islamic banks in the MENA countries is determined positively by asset size,  equity to total asset, liquidity risk and negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Equity refers to the shareholders' equity (or owners' equity for privately held banks). Alharbi (2017), Mongid (2016) and found that the equity of Islamic banking had a positive and significant impact on profitability of Islamic banks under study. Liquidity is the ability of a bank to have sufficient liquid assets i.e., cash to pay the bills and obligations on time.…”
Section: Internal Factorsmentioning
confidence: 89%
See 1 more Smart Citation
“…Equity refers to the shareholders' equity (or owners' equity for privately held banks). Alharbi (2017), Mongid (2016) and found that the equity of Islamic banking had a positive and significant impact on profitability of Islamic banks under study. Liquidity is the ability of a bank to have sufficient liquid assets i.e., cash to pay the bills and obligations on time.…”
Section: Internal Factorsmentioning
confidence: 89%
“…Senan, Noaman, Aldalaien & Al-Homaidi (2021), Abduh & Baharoon (2016 and revealed that the assets size had a significant relationship with profitability of Islamic banks under study. Alharbi (2017), Mongid (2016), Eljelly (2013), Masood & Ashraf (2012), Idris et al (2011) and Karim, Sami & Hichem (2010) pointed out that the bank size had a positive and significant impact on profitability of Islamic banks under study. Al-Homaidi, International Journal of Islamic Economics and Finance Studies, 2022/1 Tabash & Ahmad (2020), Asadullah (2017) and Zeitun (2012) indicated that the total assets had a negative and significant impact on profitability of Islamic banks under study.…”
Section: Internal Factorsmentioning
confidence: 96%
“…In addition, the authors believe that the impact of crisis was only a temporary shock rather than a structural break. Mongid (2016) investigated the determinants of profitability of Islamic banks from MENA region and how the global financial crisis impacted their performance. His study covers 117 banks for the period of 2003 to 2011.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding liquidity risk and profitability relation; increase in the current ratio and the investment ratio of the available funds have positive effects on the profitability (Malik and Aqeel, 2017) (Mongid, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%